Level of Students' Knowledge about Pulmonary TB in Elementary Schools X - Gurusinga, Rahmad (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Tuberculosis (TB) in children is an infection caused by the bacteria Mycobacterium tuberculosis with symptoms such as prolonged coughing, chest pain, and weight loss, which can interfere with children's health and growth. In terms of education, infected children often have to be absent from school to undergo treatment, which can cause learning delays and academic difficulties. Therefore, it is very important for elementary school children to know about pulmonary TB disease. This study aims to assess elementary school students' knowledge about tuberculosis (TB) and describe the demographic characteristics of the respondents. This type of research is descriptive. The research location is at Elementary School Sampling was carried out using a systematic sampling technique. The data collection instrument is a questionnaire. The results showed that the majority of respondents were aged 10–12 years (80.0%) and a small proportion were aged 6–9 years only (20.0%), the female gender was more numerous, namely (70.0%), while the male gender -men only (30.0%). Analysis of knowledge about TB shows that half of the respondents (50.0%) have poor knowledge, and only (12.5%) have good knowledge. It can be concluded that there is a need for more effective health education programs in schools to increase knowledge about TB among students, so as to reduce the risk of transmission and increase health awareness in the community.